2011
DOI: 10.1108/09696471111132504
|View full text |Cite
|
Sign up to set email alerts
|

The learning conference

Abstract: PurposeThe aim of this paper is to identify the principles and characteristics of a learning conference which uses action learning and action research (ALAR) processes to create: optimal learning for all participants through a collaborative, inclusive conference culture; further knowledge creation in publishing conference papers post‐conference through a supportive research culture.Design/methodology/approachThe 2010 World Congress of the Action Learning and Action Research Association (ALARA) is showcased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A common denominator of these the alternative models to conferences is their focus on participant‐driven, interactive conference methods, in short: that their “culture […] is participatory, not passive” (Serrat, , 5). The literature now contains multiple reports and critiques of conferences (e.g., Graham & Kormanik, ; Hatcher et al, ; Louw & Zuber‐Skerritt, ; Wiessner et al, ). Based on these experiences, conference organizers can now access several practice guides that describe how to increase learning at a conference, with Heap () and Hilliard () being only two exemplars.…”
Section: Learning At Conferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…A common denominator of these the alternative models to conferences is their focus on participant‐driven, interactive conference methods, in short: that their “culture […] is participatory, not passive” (Serrat, , 5). The literature now contains multiple reports and critiques of conferences (e.g., Graham & Kormanik, ; Hatcher et al, ; Louw & Zuber‐Skerritt, ; Wiessner et al, ). Based on these experiences, conference organizers can now access several practice guides that describe how to increase learning at a conference, with Heap () and Hilliard () being only two exemplars.…”
Section: Learning At Conferencesmentioning
confidence: 99%
“…participatory, not passive" (Serrat, 2010, 5). The literature now contains multiple reports and critiques of conferences (e.g., Graham & Kormanik, 2004;Hatcher et al, 2006;Louw & Zuber-Skerritt, 2011;Wiessner et al, 2008). Based on these experiences, conference organizers can now access several practice guides that describe how to increase learning at a conference, with Heap (1996) and Hilliard (2006) being only two exemplars.…”
mentioning
confidence: 99%
“…Emphasis has been on enabling participants to be active in the workshops and to give them time to reflect on learning as part of the conference (Hatcher, 2006;Louw, 2011;Ravn, 2011). The organization of the conferences do also correspond well with other research results: A synthesis including 79 studies using randomized controlled trials or comparison group designs showed 'that learning methods and practices that more actively involved learners in acquiring, using, and evaluating new knowledge and practices had the most positive consequences' (Trivette et al, 2009).…”
Section: Introductionmentioning
confidence: 58%
“…The argument for active learning is, if anything, stronger for adult learners (Knowles 1970). This tension between what educators preach and what they practice has not gone unnoticed (Elton 1983;Haley, Wiessner, and Robinson 2009; Kordts-Freudinger, Al-Kabbani, and Schaper 2017), and several authors have discussed the characteristics of "learning conferences" (Louw and Zuber-Skerritt 2011;Ravn 2007;Ravn and Elsborg 2007) and how to promote learning at learning and teaching conferences (Popovic and Cassidy 2018;Campbell and Popovic 2018). Some learning and teaching conferences have moved in the direction of being more interactive and include audience engagement in their selection criteria (not applicable for posters, but essential for workshops).…”
Section: Toward Learning Conferencesmentioning
confidence: 99%